Systematic revision of the genus Cerocoma Geoffroy, 1762 (Coleoptera: Meloidae: Cerocomini) - Turco, Federica; Bologna, Marco A. (Zootaxa, 2011)
The taxonomy of the Palaearctic genus Cerocoma is revised using a classical morphological approach. A catalogue to species with current synonyms, type information and repositories is provided as well as diagnostic keys to species (male and female) and subspecies (only male), illustrations of male dimorphic and diagnostic characters and detailed distribution data, including literature and collection records. The biology of Cerocoma is summarised, based on available literature and original field observations. Three new species are described and figured: Cerocoma confusa sp.n. (= C. syriaca Auctorum), C. longiseta sp.n. and C. martae sp.n. New status is assessed for two taxa: C. latreillei sterbai stat.n. and C. marginiventris stat.n. New synonymies are proposed as follows: C. syriaca Abeille de Perrin, 1880 = C. barthelemyi Baudi, 1878 syn. nov.; C. latreillei schah Kaszab, 1968 = C. latreillei sterbai Mařan, 1944 syn. nov.; C. scovitzi mirabilis Dvořák, 1993 = C. scovitzi intermedia Mařan, 1944 syn. nov. Adult morphological characters and molecular datasets (nuclear ITS2 and mitochondrial 16S) are used, separately and combined, to carry out the first attempt to elucidate the Cerocoma phylogeny, using Maximum Parsimony and Bayesian Inference. The resulted phylogeny supports the arrangement of Cerocoma into five subgenera: Cerocomina, Mesocerocoma and Metacerocoma as previously defined; the nominate subgenus, restricted to the species group of C. schaefferi Linnaeus, 1758; and Meloides Piller & Mitterpacher, 1783, recently resurrected on morphological data only.